2020
DOI: 10.1093/jac/dkaa431
|View full text |Cite
|
Sign up to set email alerts
|

The changing epidemiology of carbapenemase-producingKlebsiella pneumoniaein Italy: toward polyclonal evolution with emergence of high-risk lineages

Abstract: Background Previous studies showed that the epidemic of carbapenem-resistant Klebsiella pneumoniae (CR-KP) observed in Italy since 2010 was sustained mostly by strains of clonal group (CG) 258 producing KPC-type carbapenemases. In the framework of the National Antibiotic-Resistance Surveillance (AR-ISS), a countrywide survey was conducted in 2016 to explore the evolution of the phenotypic and genotypic characteristics of CR-KP isolates. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 26 publications
10
34
0
Order By: Relevance
“…Our data also confirmed previous reports that this clade likely spread from the USA to Europe and the Middle East (26) where it dominated the resistant KP population in some countries over several years (e.g. Italy and Israel) (18,27). Notably, the ST258/512 phylogeny also suggested that there have been multiple reversion events of L3 insertions, represented by genomes lacking a particular L3 insertion amidst a clade carrying that insertion ( Figure 3B ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our data also confirmed previous reports that this clade likely spread from the USA to Europe and the Middle East (26) where it dominated the resistant KP population in some countries over several years (e.g. Italy and Israel) (18,27). Notably, the ST258/512 phylogeny also suggested that there have been multiple reversion events of L3 insertions, represented by genomes lacking a particular L3 insertion amidst a clade carrying that insertion ( Figure 3B ).…”
Section: Resultssupporting
confidence: 92%
“…Several of the L3 insertion acquisition events (most notably of GD) are associated with subsequent clonal expansions. For example, the clade consisting largely of ST512 that encodes a GD insertion became highly successful as evident in the phylogeny and supported by multiple surveillance reports (18,27). Our data also confirmed previous reports that this clade likely spread from the USA to Europe and the Middle East (26) where it dominated the resistant KP population in some countries over several years (e.g.…”
Section: L3 Insertions Are Associated With Clonal Expansions In Mdr L...supporting
confidence: 90%
“…This endemicity was mostly caused by the successful clonal expansion of a K pneumoniae carbapenemase (KPC)-producing K pneumoniae clone and belonging to clonal complex 258. 5 Within the past decade, clonal complex 258 has been compounded by the emergence of additional KPC-producing K pneumoniae clones (eg, ST307 and ST101), 6 whereas CPE producing other types of carbapenemases (eg, OXA-48 and metalloβ-lactamases) have remained sporadic or at most been responsible for small outbreaks. 7 Since November 2018, however, a large outbreak of CPE-producing NDM-type carba penemases (NDM-CPE) emerged in Tuscany, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…However, p3347689I_1 was missing the IS CR1-aph(3 ' )-VI -IS Aba125-bla NDM-1 -Δ ble- qacEΔ1-sul1 region, suggesting an acquisition event in p3347558_1 ( Figure 1B ). Finally, we note that ST395 is a globally successful lineage that usually carries bla OXA-48 and bla KPC carbapenemase encoding-genes [ 25 ].…”
Section: Resultsmentioning
confidence: 99%